HARSH NORMS AND SCREENING FOR LOYALTY. (18th March 2015) - Berg, Nathan; Kim, Jeong‐Yoo
ABSTRACT: Norms that restrict choice sets or impose otherwise harsh requirements would seem to act as barriers to group formation by raising the costs of adherence to potential and continuing members. Contrary to that intuition, one observes a broad range of group norms in the real world that impose large costs on group members. Iannaccone provides a rationale for harsh norms as a mechanism to reduce free‐riding in supplying a club good. This paper proposes a new rationalization for harsh group norms as a mechanism under which harsh norms serve to screen out disloyal members, providing what is essentially a technology for measuring loyalty in environments where group leaders cannot reliably measure group members' loyalty. The model demonstrates that loyalty can be signalled through acts that are seemingly irrelevant to the group's core objectives and identity.